Intoxicación aguda por metotrexato: claves de su diagnóstico y prevención - Michelle Roberts; Dolores Pilar Bastard; Ana Clara Torre; Carlos Ronald Martínez Castellanos; Luis Daniel Mazzuoccolo (Revista del Hospital Italiano de Buenos Aires)
-